Peran Ekonomi Digital Dalam Perekonomian Lokal: Studi Kasus KUB Gula Kelapa Semut Organik Di Banyumas - Winda Fibriani; Anjar Umami; Dijan Rahajuni; Oki Anggraeni (Pusat Riset dan Inovasi Nasional, 2025)
Economic growth serves as a fundamental aspect of national development, typically assessed through the increases in Gross Domestic Product (GDP) and Gross Regional Domestic Product (GRDP). While it plays a crucial role in enhancing income and overall welfare, an exclusive emphasis on economic growth without considering social and political equity can lead to significant vulnerabilities. In this context, Micro, Small, and Medium Enterprises (MSMEs) are essential, as they provide substantial contributions to job creation and economic resilience, particularly in developing countries like Indonesia.This study explores the impact of e-commerce on the economic growth of MSMEs in Banyumas Regency. Utilizing a descriptive qualitative research methodology, data were collected through interviews and direct observations, supported by secondary literature. The findings indicate that the integration of e-commerce has not significantly influenced the income of MSME owners and farmers, revealing a preference for conventional business models. This situation underscores the need for a comprehensive strategy to effectively leverage digital technology to enhance the competitiveness and income of MSMEs